Advances in Information and Communication Technologies Processing and Control in Information and Communication Systems - Ilchenko, Mykhailo; Uryvsky, Leonid; Globa, Larysa (Lecture Notes in Electrical Engineering, 2019)
This book highlights the most important research areas in Information and Telecommunication Technologies as well as Radio Electronics. The respective chapters share in-depth and extended results in these areas with a view to resolving practically relevant and challenging issues including: management services and quality control, improved estimates for reliability indicators, the cryptographic technology Blockchain, research and forecasting of technological characteristics, satellite communications, multiservice transmission systems and effective technological solutions. These results can be used in the implementation of novel systems and to promote the exchange of information in e-societies. Given its scope the book offers a valuable resource for scientists, lecturers, specialists working at enterprises, graduate and undergraduate students who engage with problems in Information and Telecommunication Technologies as well as Radio Electronics. .